Air-conditioned university laboratories: Comparing CO2 measurement for centralized and split-unit systems - Hussin, M.; Ismail, M.R.; Ahmad, M.S. (Elsevier, 2017)
Universities are designed for higher education learning, and improving university indoor air quality (IAQ) is essential to the enhanced performances of students and staff members alike. The majority of IAQ problems are due to inadequate ventilation in university buildings. Carbon Dioxide (CO2) measurements have become a commonly used screening test of IAQ because measurement levels can be used to evaluate the amount of ventilation and general comfort. This paper examines CO2 field measurement for undergraduate practical classes. Ten air conditioned laboratories with ventilation were chosen for CO2 field measurement. CO2 was monitored under indoor and outdoor conditions. Indoor CO2 concentration for Laboratories 1 and 10 is observed to be higher than 1000 ppm which indicated inadequate ventilation, while other laboratories showed CO2 concentrations less than 1000 ppm. Air capacity and outdoor air were calculated based on the design documentation. A comparison between design and actual outdoor air/person values indicates that the air conditioning systems of the laboratories had adequate ventilation.